Growth Media for Mixed Multispecies Oropharyngeal Biofilm Compositions on Silicone. (9th July 2019) - Leonhard, Matthias; Zatorska, Beata; Moser, Doris; Schneider-Stickler, Berit
Abstract : Aims . Microbial colonization of silicone voice prostheses by bacteria and Candida species limits the device lifetime of modern voice prostheses in laryngectomized patients. Thus, research focuses on biofilm inhibitive properties of novel materials, coatings, and surface enhancements. Goal of this in vitro study was the evaluation of seven commonly used growth media to simulate growth of mixed oropharyngeal species as mesoscale biofilms on prosthetic silicone for future research purposes. Methods and Results . Yeast Peptone Dextrose medium (YPD), Yeast Nitrogen Base medium (YNB), M199 medium, Spider medium, RPMI 1640 medium, Tryptic Soy Broth (TSB), and Fetal Bovine Serum (FBS) were used to culture combined mixed Candida strains and mixed bacterial-fungal compositions on silicone over the period of 22 days. The biofilm surface spread and the microscopic growth showed variations from in vivo biofilms depending on the microbial composition and growth medium. Conclusion . YPD and FBS prove to support continuous in vitro growth of mixed bacterial-fungal oropharyngeal biofilms deposits over weeks as needed for longterm in vitro testing with oropharyngeal biofilm compositions. Significance and Impact of Study . The study provides data on culture conditions for mixed multispecies biofilm compositions that can be used for future prosthesis designs.